A literature review on the impact of COVID-19 pandemic towards patients living with chronic diseases - Wei Thing Sze; Siew Yung Huong; Shi Ying Oon; Idham Bin Zaharudie; Vijay A/L Sundaresen (Intelektual Pustaka Media Utama, 2022)
The coronavirus disease 2019 (COVID-19) has changed the daily living of people, especially those with chronic diseases. This study aimed to review the recent evidences on the impact of COVID-19 pandemic towards patients living with chronic diseases. The database and search engines used for this literature review are PubMed and Google Scholar. Abstracts were reviewed for relevance to the topic and a total of 17 articles were deemed pertinent to be summarised. Cancellation or postponement of medical consultations or procedures for chronic diseases was reported. Patients with chronic diseases also suffer worsening mental health. COVID-19 has also impacted the lifestyle of patients with chronic diseases due to reduced opportunity to go outdoors, inaccessible to fresh food, and disrupted sleep. Some pharmaceutical manufacturers shifted their focus to producing medical equipment and pharmaceutical preparations to fight against COVID-19. Difficulties in medication distributions owing to lockdown measures had been reported, as well as shortage of healthcare resources in delivering care for chronic diseases. A relationship between COVID-19 pandemic and worsening of chronic diseases was also reported. Evidence-based strategies are needed to better direct the management of chronic diseases during this unprecedented time and beyond, such as the use of telehealth and education on self-management of chronic diseases.